Comparative study on occupational stress among nursing staff in rural and urban healthcare institutions - Karen Jennifer, Ganasen (2019)
Background: Occupational stress was the response people may have when presented with work demands and pressures that were not equivalent to their knowledge and abilities and which challenge their ability to cope. Objective: The purpose of this study is to compare the occupational stress and explore the relationship between demographic and work variables among staff nurses from urban and rural healthcare institutions. Methodology: A total of thirty staff nurses from wards of Hospital Tengku Ampuan Afzan that randomly selected and Hospital Pekan had participated in this study. The data for the study were collected through questionnaires to determine the socio-demographic information while the “Ways of Coping with Stress Inventory” was used to identify the strategy that commonly used by nurses in managing occupational stress. Besides that, the “Nursing Stress Scale” (NSS) () was also use to compare the occupational stress among nurses in both urban and rural healthcare institutions. Following this, a salivary cortisol assessment was conducted among the first ten respondents from each healthcare institution to study the presence of stress marker cortisol in saliva of respondents when they are distressed. All data is analyzed by using “Statistical Package for Social Science” (SPSS) and ELISA kit to diagnosis the presence of cortisol in saliva. Results: In comparing the occupational stress among staff nurses in both rural and urban healthcare institutions, there is no difference in scores of work factors such as work environment, work hours, work demands and work relationship in Hospital Pekan and Hospital Tengku Ampuan Afzan. Both hospitals scores slightly similar in the mean value. Work hours scored with the highest mean value in both healthcare institutions in rural and urban area. Whereas, both hospitals scored with lowest mean value for the work environment. This shows working environment is not the contributing factor of occupational stress among nurses while working hours is the influencing factor that can cause occupational stress among nurses. Conclusion: These factors should be taken into consideration for developing stress management program among staff nurses from wards in the future.